Pengaruh Indikator Kesehatan Bank, Faktor Ekstenal dan Pertumbuhan Laba terhadap Return Saham Perbankan di Bursa Efek Indonesia - Novianti, Dian; Amendy, Diantia; Afandi, Agus (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to examine the influence of bank health indicators, external factors and profit growth on stock returns. Bank health indicators are reviewed based on risk profile, earnings and capital. Risk profile is measured using the non-performing loan (NPL) proxy, earnings are measured using the return on assets (ROA) and net interest margin (NIM) proxies, capital is measured using the capital adequacy ratio (CAR) proxy. The external factor in this research is inflation. measured by changes in inflation each year, the BI Rate and profit growth are measured by proxies for changes in profits each year. The object of this research is banking companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The sample selection technique is the purposive sampling method, research data is secondary data obtained from annual reports and financial reports of banking companies. which has been published on the IDX website (www.idx.co.id) and the company website during the 2016 - 2020 period. The research results show that macroeconomic factors, namely interest rates, have no effect on company value, while inflation has a positive effect on company value. Microeconomic factors, namely sales growth, company size and capital structure have no effect on company value.